Peran Pemerintah dalam Mendorong Perkembangan Usaha Mikro Kecil dan Menengah (UMKM): Kasus Usaha Mikro Kecil dan Menengah (UMKM) Mebel di Kabupaten Pati - , FACHRURIZA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Governments have an important role to the development of SMEs, many SMEs Pati has potential and continues to experience growth, one of which SMEs furniture. Continues to experience growth in the last five years, associated number. In 2010 there were 142 SMEs furniture, then at the end of 2013 increased to 184 SMEs furniture. this is certainly influenced by the role of government. But these roles are not visible, so it is necessary research to answer this. This research was conducted in the department of Cooperatives and SMEs, the SME owners furniture, which is then incremented by the Trade and Industry department and related agencies. Using qualitative methods to describe and explore in depth the role of government in the development of SMEs furniture. Determination of informants with purposive sampling and snowball sampling, with the location criteria and scale of business. Sources of data obtained from the primary data interviews and observations, and if the secondary data documentation, records, and archives. Then the data is processed using three components: data reduction, data display, conclusion drawing adjusted to indicator The role of government .. After processing and analyzing the data obtained it can be concluded that the government has a role in the development of SMEs furniture. Through the provision of physical infrastructure (supply of raw materials, promotion, networking / partnerships) and economic, training and equipment help, business protection and access to capital. These roles are conducted by the department of Cooperatives and SMEs as well as the offices of Trade and Industry, where the role of an impact on the increase in turnover, assets, employment and number of SMEs growing furniture. In addition, many of the findings in the field that can be used as a reference to improve the government's role in the development of SMEs in Pati regency.